RESPECTING AUTONOMY WITHOUT DISCLOSING INFORMATION - Walker, Tom (Bioethics, 2013)
There is widespread agreement that it would be both morally and legally wrong to treat a competent patient, or to carry out research with a competent participant, without the voluntary consent of that patient or research participant. Furthermore, in medical ethics it is generally taken that that consent must be informed. The most widely given reason for this has been that informed consent is needed to respect the patient's or research participant's autonomy. In this article I set out to challenge this claim by considering in detail each of the three most prominent ways in which ‘autonomy’ has been conceptualized in the medical ethics literature. I will argue that whilst these accounts support the claim that consent is needed if the treatment of competent patients, or research on competent individuals, is to respect their autonomy, they do not support the claim that informed consent is needed for this purpose.